Car science - Hammond, Richard, 1969- (New York : DK Pub., 2008)
"An under-the-hood, behind-the-dash look at how cars work"--Cover.
Includes index.
Keywords: Automobile mechanics -- Juvenile literature; Automobiles -- Motors -- Juvenile literature; Automobile mechanics; Automobiles -- Motors